Washing the brain : metaphor and hidden ideology - Goatly, Andrew, 1950- (Discourse approaches to politics, society, and culture ;, 2007)
Contemporary metaphor theory has recently begun to address the relation between metaphor, culture and ideology. In this wide-ranging book, Andrew Goatly, using lexical data from his database Metalude, investigates how conceptual metaphor themes construct our thinking and social behaviour in fields as diverse as architecture, engineering, education, genetics, ecology, economics, politics, industrial time-management, medicine, immigration, race, and sex. He argues that metaphor themes are created not only through the universal body but also through cultural experience, so that an apparently univ.